Further investigations of aquaponics using brackish water resources of the Negev desert - Samuel Appelbaum (Ecocycles, 2016)
Outdoor, floating raft aquaponic systems using the brackish waters of the Negev Desert in Israel and a fresh water control are described. 7 m2 of vegetables and herbs were grown in each recirculating system with Tilapia sp. fish. Plant growth was excellent for species such as celery, Swiss chard, spring onions and watercress, and fish health and growth were good. Growth rates for fish were, however, low, with an upper limit of 1.1 g per day and would have increased with ad libitum feeding. Water quality was well controlled, and iron chelate was added to correct chlorosis problems. Leafy growth was very good, but fruiting could be improved with the addition of potassium (K) and other micronutrients.